(untitled) (Web of Teachers: Inderscience Research, 2024)
In the article, a brief review of Kamil Khorezmi’s lyrics, oriphon and romantic ghazals, as well as some ghazals from his ghazals is written. Opinions were also expressed about the poet’s unparalleled skill in creating ghazals, his thorough study of the literary heritage of his predecessors, and his worthy continuation of the traditions of Eastern classical literature.